2020
DOI: 10.29244/jp2wd.2020.4.3.172-185
|View full text |Cite
|
Sign up to set email alerts
|

Valuasi Ekonomi Wisata Memancing di Perairan Laut Sekitar Tanjung Kait, Tangerang, Banten: Pendekatan Contingent Valuation Method dan Travel Cost Method

Abstract: Economic Valuation of Recreational Fishing Tourism in Tanjung Kait Coastal Water, Tangerang, Banten: Contingent Valuation Method and Travel Cost Method Approach Tanjung Kait, located in the north coast of Tangerang, has undeveloped tourism potential of recreational fishing on a bamboo platform in the middle of the sea. The purpose of this research was to determine the economic value of recreational fishing tourism in Tanjung Kait and to identify the influencing factors of the tourism demand in Tanjung Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Related research has also been carried out recently in several different tourist attractions, and the results of the study show that the amount to be paid by tourist visitors is not too large (only tens of thousands of rupiah). Some tourist attractions that show these results are the results of research Khoirudin and Khasanah (2018) who conducted an economic assessment of tourism objects in Parangtritis Yogyakarta, Fikri and Rahmin (2020), who conducted the same research in Bukit Matang Pala and South Kalimantan, as well as research results Setyawan et al (2020) who assessed fishing tourist attractions in the sea waters around Tanjung Kait Banten. It is further explained in Rosminiati et al (2019), which assessed the WTP of tourist attractions in Aceh, that both domestic and foreign visitors are willing to pay more if they have more income.…”
Section: Discussionmentioning
confidence: 86%
“…Related research has also been carried out recently in several different tourist attractions, and the results of the study show that the amount to be paid by tourist visitors is not too large (only tens of thousands of rupiah). Some tourist attractions that show these results are the results of research Khoirudin and Khasanah (2018) who conducted an economic assessment of tourism objects in Parangtritis Yogyakarta, Fikri and Rahmin (2020), who conducted the same research in Bukit Matang Pala and South Kalimantan, as well as research results Setyawan et al (2020) who assessed fishing tourist attractions in the sea waters around Tanjung Kait Banten. It is further explained in Rosminiati et al (2019), which assessed the WTP of tourist attractions in Aceh, that both domestic and foreign visitors are willing to pay more if they have more income.…”
Section: Discussionmentioning
confidence: 86%
“…Budi Setyawan et al (2020) showed that fishing tourism in Tanjung Kait generates an economic of IDR3,272,524,846 yearly. Similarly, Warningsih et al (2021) provided an overview of the economic potential of IDR427,140.43 per individual per visit with the resulting economic value of IDR1,507,554,457.51.…”
Section: Economic Valuementioning
confidence: 99%
“…According to (Bahamondes, 2003), incentive can be interpreted as an ability that can shape a person's desire (willingness and attitute). This approach can be used to determine the estimated rupiah value that respondents are willing to obtain these goods (Setyawan et al, 2020). According to (Prasetyawati et al, 2018), the willingness value of each individual obtained from the questionnaire can be accumulated into a holistic population value measured in Rupiah (Rp).…”
Section: Introductionmentioning
confidence: 99%